2022
DOI: 10.1002/lsm.23562
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and dermoscopic evaluation of melanocytic nevi changes during diode laser hair removal: A prospective study

Abstract: Background Laser hair removal (LHR) is a common practice with increasing use worldwide. Clinical and dermoscopic changes in melanocytic nevi after LHR have been reported but prospective studies are lacking. Objective To describe dermoscopic changes of melanocytic nevi at different time points after LHR. Methods Prospective study in a cohort of female patients undergoing diode LHR. Dermoscopic follow‐up of at least three nevi on the legs that underwent hair removal. We included three nonexposed nevi on the arms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…19 Of note, the high rate of regression in this study may be due to a longer follow up duration of 2 years and lesions noted to have changes such as bleaching or regression changes in other studies may have progressed to complete regression if followed for a longer period of time. 16 Furthermore, in the aforementioned study by Guicciardi et al, 19 follicular pigmentation and fine telangiectasias were each present in 8 (11%) of nevi surveyed, yet these findings were not noted in reports of treatment with LHR using a diode or alexandrite laser suggesting the possibility that these alterations may be unique to treatment with Nd:YAG LHR or IPL.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…19 Of note, the high rate of regression in this study may be due to a longer follow up duration of 2 years and lesions noted to have changes such as bleaching or regression changes in other studies may have progressed to complete regression if followed for a longer period of time. 16 Furthermore, in the aforementioned study by Guicciardi et al, 19 follicular pigmentation and fine telangiectasias were each present in 8 (11%) of nevi surveyed, yet these findings were not noted in reports of treatment with LHR using a diode or alexandrite laser suggesting the possibility that these alterations may be unique to treatment with Nd:YAG LHR or IPL.…”
Section: Discussionmentioning
confidence: 91%
“…10,15 Commonly reported changes in studies include complete or partial regression, decreased size, laser induced asymmetry, bleaching, darkening, and altered pattern on dermoscopy, namely changes to the reticular or dot globule pattern. 16,17 Regression, asymmetry, gray areas, and loss of pigment network were alterations reported in multiple cases. 4,10,11,[13][14][15] Nasimi et al 17 found a significant correlation between changes in color and in size, while asymmetry was correlated to changes in size only.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations